The Effect of Employee Engagement, Talent Management, and Job Satisfaction on the Performance of Inpatient Nurses at DKH Kedungwaringin Hospital in 2025 - Barokah, Ahmad; Wulandari, Sonya; Pangkey, Dicky Yulius (International Journal of Business, Law, and Education, 2026)
Nurse performance is a critical determinant of healthcare service quality, particularly in inpatient settings where nurses provide continuous and direct patient care. Challenges in service quality and patient complaints indicate the need to examine organizational factors that influence nurse performance. This study aimed to analyze the effects of employee engagement, talent management, and job satisfaction on the performance of inpatient nurses at DKH Kedungwaringin Hospital in 2025. A quantitative cross-sectional design was employed involving all 50 inpatient nurses, using total sampling. Data were collected through structured questionnaires and analyzed using multiple logistic regression with SPSS version 24.0. The results revealed that employee engagement significantly influenced nurse performance (p = 0.006; OR = 7.495), indicating that highly engaged nurses were 7.495 times more likely to demonstrate good performance. Talent management also showed a significant effect (p = 0.021; OR = 5.313), as did job satisfaction (p = 0.045; OR = 4.018). The Nagelkerke R Square value of 0.522 suggests that 52.2% of the variance in nurse performance was explained by the three predictors. Among them, employee engagement emerged as the strongest determinant. Strengthening these factors is essential for improving nurse performance and healthcare service quality.